How Much Does Industry Matter?: An Alternative Empirical Test - Powell, T (1996)
Empirical studies using Federal Trade Commission Line of Business data have reported that industry membership explains between 17  percent and 20  percent of financial performance variance among firms. This study attempts to replicate these findings using an alternative sample and a methodology based on executives' perceptions. The results support those reported in previous studies, with industry factors explaining about 20  percent of overall performance variance. Moreover, the analysis produces empirically derived industry factors, and examines their relative power in explaining industry performance variance.